The incidence of bank regulations and taxes on wages: Evidence from US states - Timothy J. Goodspeed (Center for Economic Studies and ifo Institute (CESifo), 2012)
Banks and the financial sector have come under increased scrutiny since the 2008 financial crisis. Regulations concerning the banking sector have been re-written and there have been calls for increased taxation of banks (as companies) and the remuneration of bankers. In general, two sorts of taxes are commonly mentioned, taxes on the profits of banks and taxes on bank wages. As the corporate tax may be borne by labor, a natural question to ask is whether the economic incidence of these taxes really differs. The cost of regulations can also be passed on, but public finance economists typically ignore the incidence of regulations, a potentially important source of influence for banks. This paper focusses on two questions. First, we ask whether there is an earnings premium in the financial sector. Second, we examine the issue of tax and regulatory incidence by estimating the degree to which banking regulations and company taxes on banks influence wages in the banking sector. We use individual data on wages combined with data from US states on the states' tax rates and timing of regulatory changes applied to financial corporations. We find (i) a raw 45% earnings premium in the financial sector; (ii) a negative effect of corporate tax on wages in the manufacturing sector but a positive or no effect on wages in the banking sector, and (iii) lower wages in the banking sector in states that de-regulated earlier. The tax incidence result is somewhat surprising though it is consistent with Huizinga, Voget, and Wagner (2011), who find that home country corporate income taxation of foreign-source bank income is almost fully passed through to higher interest margins charged abroad. The result may have to do with specifics of the banking industry such as market power, labor mobility, or inelastic demand and elastic supply of banking services.
Keywords: H20; G20; H70; 330; Bankenpolitik; Unternehmensbesteuerung; Finanzsektor; Steuerinzidenz; Bankberufe; Lohn; Teilstaat; USA